Pre-operative risk factors for stomal stenosis with Malone antegrade continence enema procedures. Issue 6 (December 2017) - Rensing, A.J.; Koenig, J.F.; Austin, P.F.
Summary: Introduction: The Malone antegrade continence enema (MACE) procedure remains an effective tool in providing independence to patients with refractory constipation. Appendiceal, ileal and colonic segments are all used depending upon the patient's individual anatomy and surgeon's preference. Unfortunately, MACE stomal stenosis (SS) remains a frustrating complication. It was hypothesized that SS is associated with the type of efferent limb used for MACE construction. Objective: To perform a retrospective risk analysis of the pre-operative factors that correlated with postoperative stomal stenosis. Materials and methods: The study reviewed 39 consecutive patients treated with MACE by a single surgeon at the present institution. Collected data included: the type of channel construction, stoma site, pre-operative body mass index (BMI) z -score, pre-operative diagnosis, and development of SS. Stomal stenosis was defined as a documented inability to catheterize, requirement of a Chait tube, or a subsequent stomal revision. An odds ratio (OR) analysis was performed to evaluate the association with the development of SS. Results: Stomal stenosis developed in 19 patients (49%) with an average follow-up of 4.7 years. The majority of patients had a diagnosis of myelomeningocele (90%), and there was no significant difference in gender distribution (54% males, 46% females). The distribution types of MACE efferent limbs consisted of appendicocecostomy in 20 (51%), cecal-wall flap in 16 (41%) and ileocecostomy in three patients (8%). Neither type of efferent limb, nor stomal location were significant predictors of postoperative SS. Pre-operative obesity (BMI ≥95%), however, demonstrated a significant risk of SS compared to non-obese patients (OR 4.44, 95% CI 1.08–18.4, P = 0.04). Discussion: This was a single-institution study of a relatively small number of patients. However, examining consecutive patients with a common surgeon can minimize technique variability. Also, the rates of stenosis in this cohort were higher than most. This may have been due to a more broad definition (unable to catheterize). These findings complement recent literature showing an increased complication rate for the obese pediatric patient. Conclusion: Stomal stenosis remains a frustrating complication following creation of the MACE stoma. In the present series, neither a cecal wall flap, nor the stomal site location contributed to SS. Obesity was the only identified statistically significant risk factor that led to SS. Summary Table Stomal stenosis risk analysis. Stomal composition Patent MACE Stenosed MACE Stomal location Patent Stenosed Appendix 11 9 RLQ 12 11 Cecal flap 8 8 Umbilical 8 8 Ileocecostomy 1 2 Odds ratio 1.09 Odds ratio a 1.22 P -value 0.89 P -value 0.77 Confidence interval 0.30–3.91 Confidence interval 0.32–4.57 Pre-operative weight Patent Stenosed Pre-operative weight Patent Stenosed Normal 16 9 Normal 13 8 Obese 4 10 Overweight 7 11 Odds ratio 4.44 Odds ratio 2.55 P -value 0.04 P -value 0.16 Confidence interval 1.08–18.36 Confidence interval 0.70–9.31 MACE, Malone antegrade continence enema; RLQ, right lower quadrant. a Comparing the standard (appendiceal) MACE to the cecal flap.